Intra- and interspecific sexual isolation in two sibling species of Drosophila: D. ananassae and D. pallidosa. Issue 6 (1st November 2020) - Singh, Roshni; Singh, Bashisth N.
Abstract : We tested intraspecific as well as interspecific sexual isolation in two sibling species of Drosophila: D. ananassae and D. pallidosa by the multiple-choice technique. The results indicate significant deviations from random mating in both intraspecific as well as interspecific crosses, which demonstrates the existence of strong sexual isolation. Differences in mating propensity in different strains of both the species may be hypothesized as the primary cause behind intraspecific sexual isolation. However, this result was not expected because D. pallidosa is an endemic species that exhibits a greater degree of intraspecific isolation as compared to its cosmopolitan sibling species D. ananassae . Further, both the species show a considerable degree of sexual isolation. We discuss the evolutionary status of both the sibling species in light of these results.